THE DIFFERENCES BETWEEN PUBLIC AND PRIVATE HOSPITAL WORKING CULTURES ON JOB SATISFACTION INDEX IN THE MILLENNIAL GENERATION - Yulie Erida Nur Rahmawati; Sri Suwarsi; Mohammad Rizal Chaidir; Muhardi Muhardi; Rachmat Suyanto; Dadang Kusnadi (Jurnal Riset Kesehatan, 2022)
The hospitals' issue in dealing with the healthcare service becomes challenging in the current era of the millennial generation employee. This may make interpersonal working cooperation difficult to achieve. Hence, this study attempts to evaluate the differences between public and private hospital working cultures on the job satisfaction index in the millennial generation. We used AIH public hospital and AIS private hospital in Bandung to conduct the study. All employees were of the millennial generation (born 1981-2000). The job satisfaction index includes passion, salary, supervision, work colleagues, and working conditions. It has a maximum score of 75 and a minimum score of 15. P-value 0.05 was defined as significant differences. The results showed that private hospitals have a job satisfaction index score of passion (50.22±6.51 vs. 42.32±8.01; p= 0.042), salary (51.49±11.54 vs. 27.92±6.61; p= 0.033), supervision (66.78±4.82 vs. 53.32±11.04; p= 0.073), and working conditions (61.41±7.59 vs. 37.72±9.52; p= 0.139) that are higher than public hospitals. The work colleagues’ score was the only higher in public hospitals (35.81±8.98 vs. 29.91±5.94; p= 0.040). This present study showed differences between public and private hospital working cultures on the job satisfaction index in the millennial generation.